Shale Gas Technical Development and Innovation - LİANG, Xingyuan; HU, Ji; ZHOU, Qishuang; DU, Lei; Lİ, Qiang; Lİ, Baofeng; CHENG, Yuan (International Journal of Computational and Experimental Science and Engineering, 2020)
The classical theory of geology believe that shale reservoir physical property is poor, the oil and gas could not be saved, or only as source rock cover, almost have no exploitation value. Later people found that shale belongs to in-situ large area continuous reservoirs, and put forward a series of shale gas development technology. In this paper, we base on time sequence and shale gas production, study the transition of the shale gas geology theory and shale gas development technology advances, analyzing the important role of technological innovation, in order to give some enlightenment to the development of shale gas development technology.